The Effect of the Use of THIEVES Strategy on Students’ Critical Reading Comprehension - Frisca Bella Romadany Sejati; Candra Hadi Asmara; Ribeh Najib Muhammad (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the effectiveness of the THIEVES strategy in enhancing students’ critical reading comprehension in an English as a Foreign Language (EFL) context, particularly at the senior high school level. Employing a quasi-experimental research design, the study involved two groups: an experimental group taught using the THIEVES strategy and a control group that received conventional reading instruction commonly applied in the classroom. The participants consisted of tenth-grade students of SMA Muhammadiyah 8 Gresik who were selected to represent learners with similar academic backgrounds. Data were collected through pre-tests and post-tests that were specifically designed to measure students’ critical reading comprehension skills, including their ability to identify main ideas, infer meaning, and evaluate textual information. The findings revealed that students in the experimental group showed significantly higher improvement in post-test scores compared to those in the control group. Statistical analysis using paired-sample and independent-sample t-tests confirmed that the observed improvement was statistically significant and not due to chance. These results indicate that the THIEVES strategy effectively promotes active engagement, critical analysis, and deeper comprehension of reading texts. Therefore, the strategy is strongly recommended as an effective instructional approach for improving students’ critical reading skills in EFL classrooms.